2021
DOI: 10.26434/chemrxiv.14386814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photocatalytic Deoxygenation of N–O Bonds with Rhenium Complexes: From the Reduction of Nitrous Oxide to Pyridine N-Oxides

Abstract: The accumulation of nitrogen oxides in the environment calls for new pathways to interconvert the various oxidation states of nitrogen, and especially their reduction. The large spectrum of reduction potentials covered by nitrogen oxides makes it however difficult to find general systems capable of efficiently reducing various N-oxides. Here photocatalysis unlocks high energy species able to both circumvent the inherent low reactivity of the greenhouse gas and oxidant N<sub>2</sub>O (E°(N<sub>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In recent developments, 30 the research groups led by Xu and Malkov independently reported electrochemical deoxygenation protocols. 31 In our continued effort to develop synthetic methods based on visible-light-induced photocatalysis, 32 we were drawn to the potential of photoredox catalysis to promote oxygen removal from heterocyclic N-oxides under mild conditions via single electron transfer pathways (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In recent developments, 30 the research groups led by Xu and Malkov independently reported electrochemical deoxygenation protocols. 31 In our continued effort to develop synthetic methods based on visible-light-induced photocatalysis, 32 we were drawn to the potential of photoredox catalysis to promote oxygen removal from heterocyclic N-oxides under mild conditions via single electron transfer pathways (Fig.…”
Section: Introductionmentioning
confidence: 99%